A new species of Johnstonimyia Lopes from Vanuatu (New Hebrides) (Diptera, Sarcophagidae) - Satoshi Shinonaga; Rokuro Kano (Memorias do Instituto Oswaldo Cruz, 1989)
A new species of the genus Johnstonimyia Lopes, namely J. lopesi, is described and illustrated.